A comparison of utilization design ratios of self-centering shape memory alloy with different brace configurations. (15th April 2023) - Abraik, Emad; Asif, Iqbal
Highlights: Impacts of the design utilization ratio on seismic response of different brace configurations are investigated. Four bracing configurations designed according to the National Building Code of Canada and Canadian Standard CSA S16, with two design utilization ratios are considered. Results confirm that use of a brace design with high utilization ratio can reduce material use by about 50% while maintaining the unique characteristics. FEMA P-58 residual displacement equation predicts displacements accurately for some braced frame types with high utilization ratios, whereas it overestimates the same for others. Abstract: Concentrically braced frames are common and effective systems for resisting earthquake forces in low and high-rise buildings. While various brace configurations can improve seismic performance, steel yielding causes residual drifts, which complicate or render the repair of damaged buildings irreparable. Minimizing seismic residual drifts is, therefore, imperative. The Superelastic Shape Memory Alloys (SE-SMAs) are superelastic materials capable of experiencing large plastic deformations and regaining their original shape upon unloading. Their use in steel structures reduces residual deformations associated with seismic events and will facilitate post-seismic retrofitting. The impacts of the utilization design ratio (UDR) on the seismic response of different brace configurations are investigated using two utilization design ratios (UDR1 and UDR2). The results show that using the UDR2 reduces the used SE-SMA material while maintaining the unique characteristics of SE-SMA material. Further, the FEMA P-58 equation accurately predicts residual displacements for I-VBF and M−XBF when braces are designed using UDR2 but overestimates residual displacements for VBF and XBF when the same UDR2 is used.